Grinding as Solvent-Free Green Chemistry Approach for Cyclodextrin Inclusion Complex Preparation in the Solid State - Mario Jug; Paola Angela Mura (MDPI AG, 2018)
Among the different techniques proposed for preparing cyclodextrin inclusion complex in the solid state, mechanochemical activation by grinding appears as a fast, highly efficient, convenient, versatile, sustainable, and eco-friendly solvent-free method. This review is intended to give a systematic overview of the currently available data in this field, highlighting both the advantages as well as the shortcomings of such an approach. The possible mechanisms involved in the inclusion complex formation in the solid state, by grinding, have been illustrated. For each type of applied milling device, the respective process variables have been examined and discussed, together with the characteristics of the obtained products, also in relation with the physicochemical characteristics of both the drug and cyclodextrin subjected to grinding. The critical process parameters were evidenced in order to provide a useful guide for a rational selection of the most suitable conditions for an efficient inclusion complex preparation by grinding, with the final purpose of promoting a wider use of this effective solvent-free cyclodextrin inclusion complex preparation method in the solid state.